The Impact of Age on the Association Between Physical Activity and White Matter Integrity in Cognitively Healthy Older Adults - Wolf, Dominik; Fischer, Florian U.; Riedel, David; Knaepen, Kristel; Kollmann, Bianca; Kocabayoglu, Merve; Brüggen, Katharina; Teipel, Stefan; Tüscher, Oliver; Binder, Harald; Mierau, Andreas; Fellgiebel, Andreas (Frontiers in Aging Neuroscience, 2020)
Cognition emerges from coordinated processing among distributed cortical brain regions, enabled through interconnected white matter networks. Cortical disconnection caused by age-related decline in white matter integrity (WMI) is likely to contribute to age-related cognitive decline. Physical activity (PA) has been suggested to have beneficial effects on white matter structure. However, its potential to counteract age-related decline in WMI is not yet well established. The present explorative study analyzed if PA was associated with WMI in cognitively healthy older adults and if this association was modulated by age. Forty-four cognitively healthy older individuals (aged 60-88 years) with diffusion tensor imaging (DTI) and PA measurements were included from the AgeGain study. Voxelwise analysis using tract-based spatial statistics demonstrated that PA was associated with WMI in older adults. However, results emphasized that this association was restricted to high age. The association between PA and WMI was found in widespread white matter regions suggesting a global rather than a regional effect. Supplementary analyses demonstrated an association between integrity of these regions and the performance in memory (verbal learning and memory test) and executive functioning (Tower of London). Results of the present explorative study support the assumption that PA is associated with WMI in older adults. However, results emphasize that this association is restricted to high age. Since cognitive decline in the elderly is typically most pronounced in later stages of aging, PA qualifies as a promising tool to foster resilience against age-related cognitive decline, via the preservation of the integrity of the brains WM.